Investor Protection and Corporate Valuation - La Porta, Rafael; Lopez‐De‐Silanes, Florencio; Shleifer, Andrei; Vishny, Robert (Journal of Finance, 2002)
ABSTRACT We present a model of the effects of legal protection of minority shareholders and of cash‐flow ownership by a controlling shareholder on the valuation of firms. We then test this model using a sample of 539 large firms from 27 wealthy economies. Consistent with the model, we find evidence of higher valuation of firms in countries with better protection of minority shareholders and in firms with higher cash‐flow ownership by the controlling shareholder.